Analysis of Automotive Industry Competency Needs for Automotive Engineering Education Students of Medan State University in the 4.0 Era - Doni, Rahma; Dinata, Riangga; Permana, Agus; Damanik, Hardian Sidik; Basuki, Nur (AEEJ : Journal of Automotive Engineering and Vocational Education, 2025)
The advancement of automotive technology in the Industrial Revolution 4.0 era requires vocational education graduates to possess updated competencies aligned with industry standards. This study investigates the gap between the competencies of students in the Automotive Engineering Education Program at Universitas Negeri Medan and the needs of the automotive industry. A descriptive qualitative approach was applied, involving interviews, observations, and document analysis with stakeholders from academia and industry. The findings reveal a significant misalignment, particularly in digital automotive systems, computer-based diagnostics, and soft skills such as communication and problem-solving. The study highlights the need for curriculum revision, integration of industry-based learning practices, and enhanced collaboration between educational institutions and industry partners to ensure graduate readiness in meeting modern automotive demands.